2020
DOI: 10.1126/sciadv.aax3969
|View full text |Cite
|
Sign up to set email alerts
|

The cohesin release factor Wapl interacts with Bub3 to govern SAC activity in female meiosis I

Abstract: During mitotic prophase, cohesins are removed from chromosome arms by Wapl to ensure faithful sister chromatid separation. However, during female meiosis I, the resolution of chiasmata requires the proteolytic cleavage of cohesin subunit Rec8 along chromosome arms by Separase to separate homologs, and thus the role of Wapl remained unknown. Here, we report that Wapl functions as a regulator of spindle assembly checkpoint (SAC) to prevent aneuploidy in meiosis I. Depletion of Wapl accelerates meiotic progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
7
0
1
Order By: Relevance
“…Our previous study has reported that the role of WAPL in regulation of SAC activity in mouse oocytes is mediated by a pivotal component of SAC Bub3 [ 23 ]. To ask whether this mechanism is conserved in porcine oocytes, we assessed the expression and localization of BUB3 after WAPL depletion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study has reported that the role of WAPL in regulation of SAC activity in mouse oocytes is mediated by a pivotal component of SAC Bub3 [ 23 ]. To ask whether this mechanism is conserved in porcine oocytes, we assessed the expression and localization of BUB3 after WAPL depletion.…”
Section: Resultsmentioning
confidence: 99%
“…However, interestingly, in mammalian oocytes, homologous chromosomes become paired to form a bivalent in meiotic prophase [ 6 , 26 ], and subsequently the distal cohesins on bivalent arms are stripped by Separase instead of Wapl to allow homologous chromosome segregation at anaphase I stage [ 6 , 27 ]. In our recent study, we have unexpectedly found that Wapl functions as a SAC regulator by maintaining the stability of Bub3 to orchestrate the mouse oocyte meiotic progression [ 23 ]. Nevertheless, whether this noncanonal role of Wapl in oocyte meiosis is conserved among species still needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of Bub3 also results in shorter metaphase I and metaphase II due to premature localization of protein phosphatase 1 (PP1) to kinetochores, which antagonizes Ipl1-mediated phosphorylation. A new role for the Bub1–Bub3 pathway in maintaining the balance between kinetochore localization of Ipl1 and PP1, a balance essential for accurate meiotic chromosome segregation and timely anaphase onset, has been proposed [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two crucial regulators of cell cycle, cohesin and the SAC share common regulators to coordinate faithful chromosome segregation and orchestrate meiotic progression, Research show that cohesin release factor Wapl interacts with Bub3 to mediate the SAC function in oocyte meiosis I,Nevertheless,Wapl regulates Bub3 through an unknown way that requires further investigation 19 .Other research shows that ,in meiosis, Bub3 is crucial for correction of attachment errors. Depletion of Bub3 results in reduced levels of kinetochore-localized Ipl1 and concomitant massive chromosome missegregation caused by incorrect chromosome-spindle attachments.…”
Section: Discussionmentioning
confidence: 99%